Step * 2 1 1 1 1 2 1 of Lemma equipollent-product


1. : ℤ
2. n ≠ 0
3. 0 < n
4. ∀f:ℕ1 ⟶ ℕi:ℕ1 ⟶ ℕf[i] ~ ℕΠ(f[i] i < 1)
5. : ℕn ⟶ ℕ
6. i:ℕ1 ⟶ ℕf[i] ~ ℕΠ(f[i] i < 1)
7. b1 i:ℕ1 ⟶ ℕf[i]
8. b2 : ℕf[n 1]
⊢ <λi.if (i =z 1) then b2 else b1 fi if (n =z 1) then b2 else b1 (n 1) fi >
= <b1, b2>
∈ (i:ℕ1 ⟶ ℕf[i] × ℕf[n 1])
BY
(EqCD THEN Auto) }


Latex:


Latex:

1.  n  :  \mBbbZ{}
2.  n  \mneq{}  0
3.  0  <  n
4.  \mforall{}f:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}.  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]  \msim{}  \mBbbN{}\mPi{}(f[i]  |  i  <  n  -  1)
5.  f  :  \mBbbN{}n  {}\mrightarrow{}  \mBbbN{}
6.  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]  \msim{}  \mBbbN{}\mPi{}(f[i]  |  i  <  n  -  1)
7.  b1  :  i:\mBbbN{}n  -  1  {}\mrightarrow{}  \mBbbN{}f[i]
8.  b2  :  \mBbbN{}f[n  -  1]
\mvdash{}  <\mlambda{}i.if  (i  =\msubz{}  n  -  1)  then  b2  else  b1  i  fi  ,  if  (n  -  1  =\msubz{}  n  -  1)  then  b2  else  b1  (n  -  1)  fi  >
=  <b1,  b2>


By


Latex:
(EqCD  THEN  Auto)




Home Index